Case reportCase report of African tick-bite fever from Poland - Chmielewski, Tomasz; Szymanek, Anna; Mączka, Ilona; Fiecek, Beata; Simon, Krzysztof; Tylewska-Wierzbanowska, Stanisława (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
A confirmed case of rickettsiosis acquired in South Africa and recognized in Poland was described. The patient fulfilled clinical criteria highly suggestive of African tick bite fever, such as eschars, regional lymphadenitis, cutaneous rash within 10 days after his return from sub-Saharan Africa. Infection with Rickettsia africae was confirmed by polymerase chain reaction and seque